LRFMVD : a customer segmentation model - Sagor, Kawsar Mahmud; Sadhin, Masrur Arefin; Jahan, Ishrat; Prottay, Rezwanul Karim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.